1980年代至90年代中国的自由主义理论与实践 = The theory and practice of liberalism in China in the eighties and nineties - 胡颖婷 Woo, Ying Teng (2014)
自由主义在中国是个舶来品。中国与西方国家的社会结构和发展历史不同， 因此如果把西方自由主义理论直接移植到中国社会里，就可能导致理论和实践脱节。自由主义在理论上提倡理性与和平地追求个人权利和民主，但人们在实践自由主义时往往倾向暴力，以致背离理论的意旨而引发颠覆性的结果。目前学术界虽然认识到理论和实践的差异及关系，但把自由主义理论和实践与中国社会现实结合起来分析的研究并不多。本文将通过历史论述和学者的观点探讨20世纪80至90年代中国自由主义理论和实践，探讨其对中国政治发展的价值和意义。本文认为上世纪80至90年代实践自由主义的社会条件以及知识分子政治影响力的不足，导致在中国改革关键时期自由主义理论和实践的脱节。Liberalism is one of the most influential western concepts introduced into China. However due to the differences in social fabric and development between China and its western counterparts, direct implementation of western theory into the Chinese society could cause a discrepancy between theory and practice. In theory, liberalism advocates the rational and peaceful pursuit of personal rights and democracy. However, people tend to incline towards violence when putting liberalism into practice, resulting in a deviation from its theory and causing undesired consequences. Although the academia acknowledges the difference and relation between theory and practice, there are not many studies that analyse liberalism’s theory and practice together with China’s social reality. Hence, this paper aims to uncover the value and significance of the theory and practice of liberalism to China’s political development through historical discourse and perspectives from scholars. This paper will show that the discrepancy between liberalism’s theory and practice during China’s critical period of reform is caused by the lack of social conditions and inadequate political influence by intellectuals in the eighties and nineties.